2015
DOI: 10.1007/s11894-015-0436-2
|View full text |Cite
|
Sign up to set email alerts
|

Small Intestinal Fungal Overgrowth

Abstract: Small intestinal fungal overgrowth (SIFO) is characterized by the presence of excessive number of fungal organisms in the small intestine associated with gastrointestinal (GI) symptoms. Candidiasis is known to cause GI symptoms particularly in immunocompromised patients or those receiving steroids or antibiotics. However, only recently, there is emerging literature that an overgrowth of fungus in the small intestine of non-immunocompromised subjects may cause unexplained GI symptoms. Two recent studies showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 52 publications
2
80
0
Order By: Relevance
“…All the isolates were resistant to the drug Griseofulvin. Similar resistance pattern has been reported by Olajuba and Ogunika [21].Candida albicans is a dimorphic fungus and one of the genera that cause candidiasis in humans [22] and is responsible for 50-90% of all cases of candidiasis of humans. It is a flora of the human gastrointestinal tract and is detectable in the gastrointestinal tract in 40% of healthy adults [23].…”
Section: Discussionsupporting
confidence: 82%
“…All the isolates were resistant to the drug Griseofulvin. Similar resistance pattern has been reported by Olajuba and Ogunika [21].Candida albicans is a dimorphic fungus and one of the genera that cause candidiasis in humans [22] and is responsible for 50-90% of all cases of candidiasis of humans. It is a flora of the human gastrointestinal tract and is detectable in the gastrointestinal tract in 40% of healthy adults [23].…”
Section: Discussionsupporting
confidence: 82%
“…A recent study showed that host and symbiont communities cooperatively interact to maintain the midgut microbiota in a symbiotic balance (Johnston & Rolff, 2015), suggesting that the host needs more control over symbionts by means of AMP proteins. Symbionts may become pathogenic if they grow and reproduce uncontrollably, diverting resources away from growth and other needs of the host if not controlled by the host's immune system (Erdogan & Rao, 2015;Fujimori, 2015). Importantly, the food of G. mellonella was not sterilized in this study, which makes it possible that resident microbes in the gut may be flushed away by a downstream flow of ingested content (Nyholm & McFall-Ngai, 2004;Blum et al, 2013) and replaced by opportunistic or pathogenic bacteria (Jones et al, 2013;Cariveau et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This has been difficult to verify due to the lack of specific symptoms (belching, bloating, indigestion, nausea, diarrhea, and gas) and lack of diagnostic tests. Patients considered at risk for this type of candidiasis include cancer and transplant patients receiving immunosuppressive therapy or prolonged antibiotic prophylaxis, and therefore this represents a disease associated with impaired host immunity (104,105). At the other end of the host response spectrum, experimental and clinical evidence also suggests that GI tract C. albicans colonization may be a cofactor for inflammatory diseases, which could be considered host-mediated damage.…”
Section: Non-cd4mentioning
confidence: 99%